Predictors of changes in hemodynamics associated with general anesthesia in children with atrial septal defects: a retrospective cohort study - Wakimoto, Masahiro M; Suzuki, Kenji S (Journal of Iwate Medical Assiociation, 2021)
In patients with atrial septal defects (ASD), the left ventricles are already narrow and they will likely show pre-incision hypotension (PIH) compared with healthy children. However, the risk factors of PIH have not been clarified. In this study, we examined the preoperative characteristics associated with PIH in children with ASD.One hundred and twenty patients under 16 yearsold with ostium secundum ASD were enrolled in this study. We retrospectively collected perioperative data about physical status, vital signs and echocardiographic findings. The subjects were divided into 2 groups with or without PIH and analyzed statistically.The preoperative systolic and mean blood pressure were significantly higher in the PIH group than in the no PIH group (p < 0.0001 and = 0.0022, respectively). These factors were also significantly correlated with the degree of reduction in systolic blood pressure (correlation coefficient = -0.5548 and -0.3349, respectively). However, the other characteristics, echocardiographic findings and anesthetic drugs did not significantly differ between the two groups (p > 0.05).Among the pediatric patients with ASD in this study, those with a higher blood pressure were more likely to develop PIH. However, it is difficult to predict the risk from echocardiographic findings.